MicroRNA Expression Changes and Integrated Pathways Associated With Poor Outcome in Canine Osteosarcoma - Dailey, Deanna D.; Hess, Ann M.; Bouma, Gerrit J.; Duval, Dawn L. (Frontiers in Veterinary Science, 2021)
MicroRNAs (miRNA) are small non-coding RNA molecules involved in post-transcriptional gene regulation. Deregulation of miRNA expression occurs in cancer and miRNA expression profiles have been associated with diagnosis and prognosis in many cancers. Osteosarcoma (OS), an aggressive primary tumor of bone affects approximately 10,000 dogs each year. Though survival has improved with addition of chemotherapy, up to 80% of canine patients will succumb to metastatic disease. Reliable prognostic markers are lacking for this disease. MiRNAs are attractive targets of biomarker discovery efforts due to their increased stability in easily obtained body fluids as well as within fixed tissue. Previous studies in our laboratory demonstrated dysregulation of genes in aggressive canine OS tumors that participate in miRNA regulatory networks reportedly disrupted in OS or other cancers. We utilized RT-qPCR in a 384-well plate system to measure relative expression of 190 miRNAs in 14 canine tumors from two cohorts of dogs with good or poor outcome (disease free interval > 300 days or < 100 days respectively). Differential expression analysis in this subset guided selection of candidate miRNAs in tumors and serum samples from larger groups of dogs. We ultimately identified a tumor-based 3-miR Cox proportional hazards regression model and a serum-based 2-miR model each able to distinguished patients with good and poor prognosis via Kaplan-Meier analysis with the log rank test. Additionally, we integrated miRNA and gene expression data to identify potentially important miRNA-mRNA interactions disrupted in canine OS. Integrated analyses of miRNAs in the 3-miR predictive model and disrupted genes from previous expression studies suggest contribution of the primary tumor microenvironment to the metastatic phenotype of aggressive tumors.